2008
DOI: 10.2754/avb200877030393
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Epidemiology of Bovine Brucellosis in Punjab (India) Using Milk-ELISA

Abstract: Bovine brucellosis, caused by Brucella abortus, is a serious zoonotic disease manifested by reproductive disorders resulting in huge economic losses to dairy farmers. A random survey was conducted to study the epidemiology of brucellosis in Punjab (India) using sampling software Survey Toolbox. Two-stage sampling procedure was adopted; in the first step, villages were selected randomly from sampling frame of all the villages of Punjab followed by selection of owners, and animals in individual farms were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 7 publications
9
44
0
Order By: Relevance
“…This result were concurred with Bachh et al, 1988, Isloor et al, 1998and Aulakh et al, 2008whereas Dhand et al, (2005 in Punjab also recorded higher prevalence of brucellosis in animals with a history of abortion (33.87%) than in those without such a history (11.63%). It obviously concluded that the Brucella is the major etiological agent for abortion in farm animals.…”
Section: Association Of Previous Reproductive Disorders With Prevalensupporting
confidence: 82%
See 1 more Smart Citation
“…This result were concurred with Bachh et al, 1988, Isloor et al, 1998and Aulakh et al, 2008whereas Dhand et al, (2005 in Punjab also recorded higher prevalence of brucellosis in animals with a history of abortion (33.87%) than in those without such a history (11.63%). It obviously concluded that the Brucella is the major etiological agent for abortion in farm animals.…”
Section: Association Of Previous Reproductive Disorders With Prevalensupporting
confidence: 82%
“…The low prevalence in Non-Descript breeds might be due to natural genetic resistant pattern, adoption in field environment and innate immunity (Aulakh et al, 2008).…”
Section: Breed-wise Prevalence Of Bovine Brucellosismentioning
confidence: 99%
“…Whereas, Patel [16] and Aulakh . [17] recorded still higher animal prevalences on milk tests with corresponding figures of 28.30 and 18.26%, respectively. Whereas, few reports from India and neighboring country reported animal prevalence below 10% , the animal prevalence (11.90%) observed in present study was found higher than a wide area based bovine brucellosis prevalence (6-7%) by ELISA conducted by Renukaradhya .…”
Section: Introductionmentioning
confidence: 83%
“…The disease prevalence data were obtained from serological surveys (Aulakh et al, 2008;Kollannur et al, 2007;Lone et al, 2013;Shome et al, 2006;Thoppil, 2000) and livestock population data from official records (Table 1-supplementary material) (DAHD & F, 2010). Many input parameters such as decrease in carcass weight, milk production and draught power, life expectancy and reproductive rates were obtained from the published scientific literature (Table 1supplementary material).…”
Section: Methodsmentioning
confidence: 99%
“…First recorded in India in 1887 (IVRI, 1977), brucellosis has now become endemic throughout the country with prevalence of the disease ranging from 6.5% to 16.4% in different species of livestock (Aulakh et al, 2008;Kollannur et al, 2007;Lone et al, 2013;Shome et al, 2006;and Thoppil, 2000). Many factors such as absence of a control policy, failure to vaccinate young female calves, non implementation of test and slaughter, ban on cow slaughter in many Indian states, absence of treatment regimen and usual practice of selling positive reactor animals to other farmers are responsible for the spread of this disease among livestock in India.…”
Section: Introductionmentioning
confidence: 99%